Temperate Cereal Improvement for Sustainable Agriculture Powdery Mildew Resistence in Barley Lines (Powdery Mildew, Erysiphe graminis DC. ex Merat hordei Marchat) - Ngamchuen Ratanadilok (Agriculture and Natural Resources, 1993)
During 1991-92, several promissing barley lines from the Temperate Cereal Improvement project were tested in replicated trial for grrain yield potential for malt quality and diseases at the Royal Angkhang stations. Seed samples were taken from the selected lines to Denmark in 1992 for further tests both in the green house for powdery mildew reaction and in the laboratory for final malt quality. The results indicated that there were some high potential barley lines concerning malt quality and disease resistance. Thai 1,2,4 and Thai 5 were powdery mildew resistance with different genetic background and the Thai 2 and 5 were both resistance to the disease and acceptable for malt quality.